Rainbow Connection Number Pada Operasi Graf - Yulianti S, Arnasyitha; Dafik, Dafik (Prosiding Seminar Matematika dan Pendidikan Matematik, 2014)
An edge-colouring of a graph G is rainbow connected ifÂ there are k internally vertex-disjoint paths joining them, with no two edges on the path have the same color. Let G be a simple graph and f be an edge coloring, where f:E(G) ightarrow1,2,...,k,,, kinN, and the adjacent edges may have the same colour. The rainbow connection numbers of a connected graph G, denoted by rc(G), is a minimal numbers of color G required to make a rainbow connection. This paper discussed rainbow connection for any special graph, namely graph P_notimes H_2,2 and graph P_3otimes C_n.